Intelligent approaches for the synthesis of petrophysical logs - Rezaee, M. Reza; Kadkhodaie-Ilkhchi, A.; Alizadeh, P. (Institute of Physics Publishing, 2008)
Log data are of prime importance in acquiring petrophysical data from hydrocarbon reservoirs. Reliable log analysis in a hydrocarbon reservoir requires a complete set of logs. For many reasons, such as incomplete logging in old wells, destruction of logs due to inappropriate data storage and measurement errors due to problems with logging apparatus or hole conditions, log suites are either incomplete or unreliable. In this study, fuzzy logic and artificial neural networks were used as intelligent tools to synthesize petrophysical logs including neutron, density, sonic and deep resistivity. The petrophysical data from two wells were used for constructing intelligent models in the Fahlian limestone reservoir, Southern Iran. A third well from the field was used to evaluate the reliability of the models. The results showed that fuzzy logic and artificial neural networks were successful in synthesizing wireline logs. The combination of the results obtained from fuzzy logic and neural networks in a simpleaveraging committee machine (CM) showed a significant improvement in the accuracy of theestimations. This committee machine performed better than fuzzy logic or the neural network model in the problem of estimating petrophysical properties from well logs.